알츠하이머병 환자의 전반적 피질 위축, 내측두엽 위축, 백질 고강도 신호와 인지기능의 연관성 - 최린; 주수현; 이창욱; 백인호; Choi, Leen; Joo, Soo-Hyun; Lee, Chang-Uk; Paik, In-Ho (Journal of the Korean Society of Biological Psychiatry, 2015)
Objectives The aim of this study is to investigate the correlation between degenerative changes in brain [i.e., global cortical atrophy (GCA), medial temporal atrophy (MTA), white matter hyperintensities (WMH)] and neurocognitive dysfunction in Korean patients with Alzheimer's disease. Methods A total of 62 elderly subjects diagnosed with Alzheimer's disease were included in this study. The degenerative changes in brain MRI were rated with standardized visual rating scales (GCA or global cortical atrophy, MTA or medial temporal atrophy, and Fazekas scales) and the subjects were divided into two groups according to the degree of degeneration for each scale. Cognitive function was evaluated with Korean version of the Consortium to Establish a Registry for Alzheimer's Disease (CERAD-K) and several clinical features, including apolipoprotein E ${ε}4$ status, lipid profile and thyroid hormones, were also examined. Chi-square test and Fisher's exact test were performed to analyze the relationship between the degree of cerebral degeneration and neurocognitive functions. Results Demographic and clinical features, except for the age, did not show any significant difference between the two groups divided according to the degree of cerebral degenerative changes. However, higher degree of GCA was shown to be associated with poorer performance in verbal fluency test, word list recall test, and word list recognition test. Higher degree of MTA was shown to be associated with poorer performance in Mini-Mental State Examination in the Korean Version of CERAD Assessment Packet (MMSE-KC), word list recognition test and construction praxis recall test. Higher degree of white matter hyperintensities was shown to be associated with poorer performance in MMSE-KC. Conclusions Our results suggest that severe brain degeneration shown in MRI is associated with significantly poorer performance in neurocognitive tests in patients with Alzheimer's disease. Moreover, the degree of GCA, MTA and white matter hyperintensities, represented by scores from different visual rating scales, seems to affect certain neurocognitive domains each, which would provide useful information in clinical settings.